Porridge poetry - Lofting, Hugh, 1886-1947 (Salt Lake City, UT : Project Gutenberg, 2025)
"Porridge Poetry: Cooked, Ornamented and Served Up by Hugh Lofting" by Hugh Lofting is a whimsical collection of children's poetry written in the early 20th century. This book showcases a delightful array of playful verses that explore themes of food, nature, and the imagination, presented with Lofting's signature lighthearted and humorous style. The poems are designed to amuse and engage young readers, blending simple narratives with imaginative scenarios. The collection features a variety of characters and whimsical situations, such as the Porridge Poet who concocts rhymes from kitchen ingredients, and the dancing Lollipopinjay who embodies joy and liveliness. Each poem is vividly illustrated and brings whimsical stories to life, from a pirate navigating the kitchen sink to a vegetable school where turnips learn manners. With a light tone and imaginative storytelling, "Porridge Poetry" serves as both an engaging read for children and a playful celebration of the joy found in everyday life and culinary adventures. (This is an automatically generated summary.)
Illustrated by the author.
Release date is 2025-03-19
Carol Brown, Mary Glenn Krause and the Online Distributed Proofreading Team at https://www.pgdp.net (This file was produced from images generously made available by the Library of Congress)
Keywords: Children's poetry, English